Characteristics and Impacts of Sexual Violence Against Men and Boys in Conflict and Displacement: A Multicountry Exploratory Study. Issue 9 (May 2022) - Chynoweth, Sarah K.; Buscher, Dale; Martin, Sarah; Zwi, Anthony B.
Evidence of sexual violence against men and boys in many conflict-affected settings is increasingly recognized. Yet relatively little is currently known about the varied forms, sites, and impacts of this violence. Further, scant research on sexual violence against men and boys in displacement contexts has been undertaken to date. To begin to address these knowledge gaps, we undertook a multicountry, qualitative, exploratory study to gain insights into these issues. Study settings and populations were Rohingya refugees in Bangladesh; refugees and migrants who had traveled through Libya residing in Italy; and refugees from eastern Democratic Republic of the Congo (DRC), Somalia, and South Sudan residing in Nairobi and Mombasa, Kenya. Methods included 55 semi-structured focus group discussions with 310 refugees and semi-structured key informant interviews with 148 aid workers and human rights experts. Data were thematically analyzed using NVivo 12. Findings suggest that sexual violence against men and boys may not be rare in Myanmar (northern Rakhine state), Libya, eastern DRC, and South Sudan. Frequently reported forms of violence in these settings were genital violence, forced witnessing of sexual violence, and rape. Sites where violence was often reported included border crossings, along the roadside, and during imprisonment. In host countries, forms of sexual violence included sexual abuse of boys, sexual exploitation particularly of adolescents and persons with diverse sexual orientation and gender identity, and rape. Impacts on survivors involved short- and long-term physical, mental, economic, and familial dimensions. These findings aim to inform sexual violence-related prevention, mitigation, and response efforts in humanitarian settings. More research is warranted, including on sexual violence against men and boys in Somalia, sexual violence by family and community members in conflict and displacement settings, sexual exploitation of adolescent boys, and sexual violence including sexual exploitation of persons with diverse sexual orientation and gender identity.